Biocontrol of Anthracnose Disease on Chili Pepper Using a Formulation Containing Paenibacillus polymyxa C1 - Suprapta, Dewa Ngurah (Frontiers in Sustainable Food Systems, 2022)
Anthracnose disease on chili pepper has been known to seriously interfere with the plant growth and obviously reduce the yield. The disease is caused by Colletotrichum spp. In Bali Island, Indonesia six species of Colletotrihum have been identified namely Colletotrichum scovillei, C. acutatum, C. nymphaeae, C. gloeosporioides, C. truncatum, and C. fructicola. However, among them the C. scovillei was found to be the most prevalent cause of anthracnose on chili pepper in Bali, Indonesia. Two species of antagonist against C. scovillei namely Paenibacillus polymyxa C1 and Bacillus siamensis C7B have been identified as antagonist against C. scovillei. In this study the effectiveness of P. polymyxa C1 formulation was evaluated under green house condition on chili pepper cultivars Cabe Besar. Application of formulation was conduted by mini handsprayer once to five times with a week interval. Results of the study showed that treatmnet with five applications significantly (p<0.05) reduced the disease incidence, disease intensity and the yield lost of chili pepper cultivar Cabe Besar. Close relationship were observed between the number of application with disease intensity with coefficient of determination (R2) at 0.929. These results revealed that the formulation of P. polymyxa C1 effectively control the anthracnose disease on chili pepper particularly on chili pepper cultivar Cabe Besar and thus can be recommended for field testing to confirm its stability under field condition.